Muḥāsabah Al-Qur'an: Penafsiran dan Penerapannya sebagai Self-Healing Manusia Modern - Zainal Muttaqin; Amaliatus Solikhah Solikhah; Desty Rahmawati Rahmawati; Ach. Shodiqil Hafil (Indonesian Journal of Humanities and Social Sciences, 2023)
This article discusses the concept of muḥāsabah in the Qur'an and its relevance as a self-healing tool for modern humans. The concept of muḥāsabah refers to self-introspection, evaluation, and consideration of one's actions and behavior. In the context of the Qur'ān, muḥāsabah is an important concept that teaches individuals to reflect on their actions, identify mistakes, and improve themselves. This article profoundly reviews Qur'anic verses emphasizing the importance of muḥāsabah in daily life. In addition, the article also discusses its relevance in the context of modern society, which often faces stress, anxiety, and mental well-being issues. Through a deep understanding of the concept of muḥāsabah, modern man can use it as a self-healing tool to overcome various mental and emotional challenges. This article will explain how muḥāsabah can help individuals develop self-awareness, improve quality of life, and achieve better well-being. By blending religious insights and modern psychology, this article illustrates how the concept of muḥāsabah in the Qur'ān can be a valuable guideline for self-healing and personal growth of modern man. The practical implications of this understanding are improved mental well-being, the establishment of healthier social relationships, and positive contributions to society as a whole.